TARGETED APPROACH TO PROVIDING INFORMATION TO SOLVE PROBLEMS - G. G. Balayan (Модернизация, инновация, развитие)
The article outlines the main provisions of a targeted approach to managing systems give results based on information and logical models to structure and standardize the information for decision-makers regardless of the complexity of problems, their specific content and level of detail.